AYURVEDIC MANAGEMENT OF VISPHOTAKA: A CASE STUDY - Afroja Yeasmin Akhtar Roji,; Abichal Chattopadhyaya, (International Journal of Ayurveda and Pharma Research, 2020)
Visphotak is characterized with Agnidagdhanibha (Burning sensation feels like burned by fire), Sphota (white or red color nodular lesion along with clear fluid), Swajwara (persisting fever) which spreads all over the body all over the body. A six years old male, came into the OPD of Syamadas Vaidya Shastra Pith Hospital at Kolkata, presenting with complaints of generalized Blisters (vesicle) over the body associated with Osha (burning sensation all over the body), Arti (pain), mild fever, Kandu and oozing since last three months. Karma or treatment depends on Dosaswabhava. After treatment, vesicles were completely resolved with no sign of relapse and some scar marks. Photographs were taken before and after completing treatment of 3 months only after getting the patients consent. The outcome was a combined effect of both Shaman-sodhan and Ropana (through Prakshalan) therapy along with Pathya sevan. Hence, it was concluded that application of treatment principle of Pittaja Visarpa was justified in Visphotaka.